Alpha‐lipoic acid downregulates TRPV1 receptor via NF‐κB and attenuates neuropathic pain in rats with diabetes. (16th March 2020) - Zhang, Bing‐Yu; Zhang, Yi‐Lian; Sun, Qian; Zhang, Ping‐An; Wang, Xi‐Xi; Xu, Guang‐Yin; Hu, Ji; Zhang, Hong‐Hong
Abstract: Aims: Painful diabetic neuropathy (PDN) is a refractory complication of diabetes. The study aimed to investigate the role of α‐lipoic acid (ALA) on the regulation of transient receptor potential vanilloid‐1 (TRPV1) in dorsal root ganglion (DRG) neurons of rats with diabetes. Methods: Whole‐cell patch‐clamp recordings were employed to measure neuronal excitability in DiI‐labeled DRG neurons of control and streptozotocin (STZ)‐induced diabetic rats. Western blotting and immunofluorescence assays were used to determine the expression and location of NF‐κBp65 and TRPV1. Results: STZ‐induced hindpaw pain hypersensitivity and neuronal excitability in L4‐6 DRG neurons were attenuated by intraperitoneal injection with ALA once a day lasted for one week. TRPV1 expression was enhanced in L4‐6 DRGs of diabetic rats compared with age‐matched control rats, which was also suppressed by ALA treatment. In addition, TRPV1 and p65 colocated in the same DRG neurons. The expression of p65 was upregulated in L4‐6 DRGs of diabetic rats. Inhibition of p65 signaling using recombinant lentiviral vectors designated as LV‐NF‐κBp65 siRNA remarkably suppressed TRPV1 expression. Finally, p65 expression was downregulated by ALA treatment. Conclusion: Our findings demonstrated that ALA may alleviate neuropathic pain in diabetes by regulating TRPV1 expression via affecting NF‐κB.